All Days 1999
DOI: 10.2118/53939-ms
|View full text |Cite
|
Sign up to set email alerts
|

ORIMATITA®. An Improved Hematite for Drilling Fluids

Abstract: This paper was prepared for presentation at the 1999 SPE Latin American and Caribbean Petroleum Engineering Conference held in Caracas, Venezuela, 21–23 April 1999.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Tovar et al tested hematite natural deposits in Venezuela, and all the tests’ results confirmed the previous conclusion on both laboratory and field scales with an additional benefit of hematite causing less formation damage and lower environmental impact. The abrasiveness was higher than Barite but did not have a huge impact on the conducted field trials . Fadl et al used delaminated iron ore (hematite-Barite) as a weighting material and investigated its performance on density, fluid loss, filter cake, stability, and rheological properties .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tovar et al tested hematite natural deposits in Venezuela, and all the tests’ results confirmed the previous conclusion on both laboratory and field scales with an additional benefit of hematite causing less formation damage and lower environmental impact. The abrasiveness was higher than Barite but did not have a huge impact on the conducted field trials . Fadl et al used delaminated iron ore (hematite-Barite) as a weighting material and investigated its performance on density, fluid loss, filter cake, stability, and rheological properties .…”
Section: Introductionmentioning
confidence: 99%
“…The abrasiveness was higher than Barite but did not have a huge impact on the conducted field trials. 13 Fadl et al used delaminated iron ore (hematite-Barite) as a weighting material and investigated its performance on density, fluid loss, filter cake, stability, and rheological properties. 14 The delaminated iron ore consists mainly of Fe 2 O 3 and BaO (i.e., 69.76 and 14.17%, respectively), and it has a specific gravity equal to 4.67.…”
Section: Introductionmentioning
confidence: 99%
“…The crystal-structure hematite (Fe 2 O 3 ) with a specific gravity of 4.7 g/cm 3 has been practically applied with some benefits such as enhancing the rate of penetration, reducing the effect of weighting agents on rheological properties, and lowering the need of high solids content. The higher abrasiveness of hematite can be avoided by optimizing its particle size with less than 45 μm. , However, in high-pressure high-temperature conditions, where higher density mud is required to suppress the formation pressure, the settling rate of solids is increased …”
Section: Introductionmentioning
confidence: 99%
“…Iron oxide, known as hematite, has emerged as a potential substitute for barite as a densifying additive 27 . Hematite possesses a slightly greater density relative to barite, rendering drilling fluids comparable in rheological attributes to barite-containing formulations 28 . However, hematite is beset by inherent shortcomings, notably its susceptibility to magnetism and pronounced abrasiveness, as documented in several sources 27,29,30 .…”
mentioning
confidence: 99%